PENDAMPINGAN KELOMPOK USIA DINI (PAUD TERPADU FAST STAR) DALAM KEGIATAN PENANAMAN DI PANTAI SULI KABUPATEN MALUKU TENGAH - Siahaya, Ludia; Tjoa, Marthina; Lelloltery, Henderina; Sitanala, Merlin; Talakua, Christina (Universitas Pattimura, 2024)
Early age group assistance (Fast Star Integrated PAUD) aims to motivate and shape children's character from an early age to love nature and preserve the environment. This mentoring and field practice approach while learning was chosen to provide knowledge, understanding and skills to students about the importance of a tree or plant for human life and the natural environment. The stages of implementing this activity include Seed Preparation, Land Preparation, Seedling Transportation, Socialization about the Importance of Trees for Life, and Planting. Students gave a positive response to the importance of trees for life by asking questions and answering questions given during socialization. In addition, the motivation given to the students aroused their enthusiasm to carry out planting at Suli Beach and around their respective homes.